When more competition may damage welfare with socially responsible firms - Fanti, Luciano; Buccella, Domenico (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Considering a Cournot monopoly/duopoly model with linear/quadratic production costs and Corporate Social Responsibility (CSR) activities, this note shows that, in contrast to the common view, entry may reduce social welfare. Moreover, we remark that the higher the CSR activities are, the more likely the welfare-damaging entry effect may occur, and the social welfare changes following a firm’s entry crucially depend on the degree of convexity of the cost function
Keywords: monopol; duopol; dobrobyt